Pemikiran Ekonomi Ilmuwan Muslim Periode Menengah - Fikri Novrial Azhar; Nur Khiba Sania; Mohammad Miefta Ismail; Muhammad Taufiq Abadi; Muhammad Aris Syafi'i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In the middle period (around the 8th to 14th centuries AD), Muslim scientists made significant contributions in various fields, including economics. The economic thinking of Muslim scientists is reflected in their works that created the foundations of Islamic economic theory. Muslim scientists emphasized Islamic principles in the context of economics. Principles such as justice, social solidarity, and adherence to Islamic law (sharia) became the foundation for their economic thinking. They emphasized that economic activities should be carried out in accordance with Islamic moral and ethical principles. Muslim scholars present a balanced view of the role of the state and the market. They recognize the importance of state intervention to ensure equitable distribution and prevent exploitation. On the other hand, they also appreciate the role of the market as a mechanism to motivate production and resource allocation. The concepts of zakat (compulsory donation) and infaq (voluntary donation) are considered as powerful economic instruments in achieving social welfare goals. Muslim scholars viewed the obligation to give zakat as a way to reduce social inequality and empower the underprivileged. The economic thinking of Muslim scholars of this middle period provided the basis for the development of an Islamic economic system that inspired many modern economic thinkers.